2019
DOI: 10.1080/10942912.2019.1651737
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite accumulation during storage of tomato fruit as prevented by hydrogen gas

Abstract: The adverse effects of intake nitrite upon human health are well known. However, eating fruits and vegetables is one of the main pathways to absorb nitrite because of nitrogen assimilation in plants. This study demonstrated that during storage of tomato fruit, the production of endogenous hydrogen (H 2 ) was decreased, in parallel with nitrite accumulation and the senescence rate. Furthermore, exogenously applied H 2 could delay the decreased fruit H 2 production and senescence, but importantly, nitrite accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Ample evidence showed that HRW has positive effects on postharvest physiology. For example, HRW can prolong the shelf life (Hu et al, 2014) and decrease nitrite accumulation of fruits during storage (Zhang et al, 2019), as FIGURE 2 | Changes in vase life, relative fresh weight (RFW), and flower diameter of cut carnations and dissolved H 2 in solution subjected to MgH 2 , citrate buffer solution (CBS), MgH 2 -CBS, heated MgH 2 -CBS, and hydrogen-rich water (HRW). (A) Representative photographs of cut flowers (scale bar = 2 cm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ample evidence showed that HRW has positive effects on postharvest physiology. For example, HRW can prolong the shelf life (Hu et al, 2014) and decrease nitrite accumulation of fruits during storage (Zhang et al, 2019), as FIGURE 2 | Changes in vase life, relative fresh weight (RFW), and flower diameter of cut carnations and dissolved H 2 in solution subjected to MgH 2 , citrate buffer solution (CBS), MgH 2 -CBS, heated MgH 2 -CBS, and hydrogen-rich water (HRW). (A) Representative photographs of cut flowers (scale bar = 2 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence showed that HRW has positive effects on postharvest physiology. For example, HRW can prolong the shelf life ( Hu et al, 2014 ) and decrease nitrite accumulation of fruits during storage ( Zhang et al, 2019 ), as well as prolong the vase life of cut flowers ( Ren et al, 2017 ; Su et al, 2019 ; Wang et al, 2020 ). Importantly, the HRW is presently mainly obtained by water electrolysis, which requires a hydrogen gas generator.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, postharvest H 2 treatment can be beneficial for the preservation of horticultural products. Pretreatment with HRW by soaking fruits (such as kiwifruit [17], tomato [47], and lychee [18] as well as fresh-cut kiwifruit [48]) for less than 30 min can significantly maintain storage quality and prolong shelf life. H 2 fumigation for pretreatment or throughout storage period can achieve similar effects in kiwifruit [22] (Figure 1) and Chinese chive [21].…”
Section: The Timing Of Application And/or Growth Stagesmentioning
confidence: 99%
“…Moreover, HRW regulated the transcripts of long-distance transporters (BcNRT1.5 and BcNRT1.8) to reduce nitrate transport to shoots, resulting in decreased nitrate content in edible parts of seedlings. During postharvest storage of tomatoes, HRW can also decrease nitrite accumulation by either inhibiting or enhancing the activities and transcripts of NR and nitrite reductase (NiR), respectively [47].…”
Section: H 2 Is Involved In Carbon and Nitrogen Metabolismmentioning
confidence: 99%
“…Further studies have revealed that H 2 played an important role in defense responses of plants to abiotic stresses [ 13 , 14 , 15 ], plant growth [ 16 ], and secondary metabolism [ 17 ]. H 2 was beneficial to postharvest preservation of fruits (kiwifruit [ 18 , 19 ] and tomato [ 20 ]) and cut flowers (rose [ 21 ], lily [ 22 ], and Lisianthus [ 23 ]). Previous studies have reported that H 2 , dissolved in water [ 24 ] or supplied by a H 2 -releasing material (magnesium hydride [MgH 2 ]) [ 25 , 26 ], can prolong the vase life of cut carnation ( Dianthus Caryophyllus L.) flowers by enhancing activities of antioxidant enzymes and by the involvement of other gaseous signaling molecules (including nitric oxide and hydrogen sulfide).…”
Section: Introductionmentioning
confidence: 99%